Synoptic revision of the genus Cyrtorchis Schltr. (Angraecinae, Orchidaceae) in Central Africa, with the description of a new species restricted to submontane vegetation - Azandi, Laura; Stevart, Tariq; Sonké, Bonaventure; Simo-Droissart, Murielle; Avana, Marie-Louise; Droissart, Vincent (Phytotaxa, 2016)
As a preliminary step to the taxonomic revision of the genus Cyrtorchis, a synoptic revision of the species occurring in Central Africa was undertaken. Based on a detailed examination of 1,039 herbarium specimens, including nomenclatural types, we have recognized 14 species in Central Africa (one of which is divided into two subspecies), including one new species that the study brought to light, described here as Cyrtorchis submontana. The new species closely resembles C. guillaumetii and C. brownii in general aspect, but differs from them in having thinner, small elliptic leaves and shorter, fewer-flowered, more lax inflorescences with shorter bracts. The species is restricted to submontane vegetation of Central Africa and is assessed as Endangered following the IUCN Red List Categories and Criteria. Cyrtorchis latibracteata and C. subcylindrifolia are lectotypified, and the latter is placed as a synonym under C. henriquesiana. Many new records are reported, and for each taxon the distribution, habitat and ecology are given. An identification key for the Central African taxa is also provided.